Singing pedagogy and contemporary vocal music: A troubled relationship - Alessandroni Betancor, Nicolás Jesús (2017)
In this paper, we explore the interrelationships between knowledge construction in the field of Vocal Pedagogy and compositional forms of the academic music of the 20th century. We propose that research logics within Vocal Technique contributed to the thinking of the time providing a matrix to consider the vocal instrument from an objectivist position. The importance of the inquiries presented lies on the slow expansion that contemporary vocal music acquired in the last years, and in the absence of a Vocal Technique teaching method that considers the particular characteristics of this repertoire. As a current challenge, we consider necessary to chart a new model in Vocal Technique that favors the interpretation of the vocal repertoire of the 20th Century, and to establish a corpus of knowledge about (i) which are the new required skills and abilities, (ii) how they are produced, and (iii) how they should be taught.